A physics-based compact model of shield gate trench MOSFET. (January 2023) - Jiang, Yixun; Qiao, Ming; Guo, Yin; Zheng, Zuquan; Shen, Lijun; Liu, Xinxin; Zhang, Sen; Li, Zhaoji; Zhang, Bo
Abstract: This paper develops a physics-based compact model of shield gate trench (SGT) MOSFET, including a drift region current, an analytical intrinsic drain potential and a charge on the capacitance between shield gate (SG) and the drift region. In order to describe the depletion in the drift region caused by SG, a drift region current model including velocity saturation is proposed to obtain I–V characteristics. An analytical model of the intrinsic drain potential is used for the charge model to correct C GD in the off-state, and a charge on the capacitance between SG and the drift region is added to the model to obtain precise C DS . The proposed charge model can capture the behaviors of the capacitance saturation caused by SG. The experimental data of 45V SGT MOSFET on I–V, C–V, Q G and transient characteristics demonstrates the accuracy of the presented model.